Nutritional value, fermentation losses and aerobic stability of elephant grass (Pennisetum purpureum Schum.) silage treated with exogenous fibrolytic enzymes - Lemos, Maikon Figueredo (2020)
The aim of this study was to evaluate nutritional value, fermentation losses, and aerobic stability of elephant grass silage (Pennisetum purpureum Schum.) treated with exogenous fibrolytic enzymes. The experiment was conducted in a completely randomized design with four replicates (experimental silos) and five levels of fibrolytic enzymes (0, 1.5, 3.0, 4.5 and 6.0%). For this, the elephant grass was ensiled at 70 days of age in plastic buckets with 20L capacity. Silos were opened 60 days after sealing. Analyses were made for chemical composition, in vitro dry matter digestibility (IVDMD), effluent losses (EL), gas losses (GL) and dry matter recovery (DMR), as well as the aerobic stability of the silage. Data were analyzed with PROC REG of SAS® University, at 5% probability. There was an increase in IVDMD content (p < 0.0001) and reduction in NDF and ADF contents (p < 0.0001) according to enzyme levels. These results were related to the increase in the degradation of fiber fractions. There were higher EL (p = 0.0062) as a function of enzyme levels and aerobic deterioration after silo opening, at all levels tested. Thus, it can be concluded that the exogenous fibrolytic enzymes change the chemical composition of elephant grass silage, and increase its digestibility and nutritional value. Moreover, when used alone as an additive, fibrolytic enzymes are not able to recover all dry matter of this silage (with effluent and gas losses), and are not able to maintain aerobic stability in the first hours after opening the silos.